The Analysis of Ship Stability of Ferry Ro-Ro Based on Loadcase Changes - Nurhasanah; Egi Yuliora (WAVE: Jurnal Ilmiah Teknologi Maritim, 2026)
The design of Ro-Ro ferries with low payload capacities requires a more detailed analysis, as it significantly influences vessel comfort during navigation. This study presents a case study of ferries operating on the short Bengkalis – Sungai Pakning route as an alternative solution, addressing the frequent fluctuations in passenger and vehicle demand. Consequently, during peak periods, the existing Ro-Ro capacity becomes insufficient, leading to extensive queues. Conversely, during low-demand periods, the current vessels become economically inefficient, as they often delay departure until reaching full capacity to prevent operational losses. The proposed solution involves a comparative analysis of three ship models with varying load capacities to identify the optimal configuration in terms of stability and speed performance. Utilizing an analytical modeling approach, the results indicate that Model-1 exhibits superior stability performance, characterized by principal dimensions of L = 42.3 m, B = 11.8 m, H = 3.1 m, T = 2.03 m, and a payload of 78.25 tons.